Prevalence of Diabetes among Tuberculosis Patients and Associated Risk Factors in Kathmandu Valley - Thapa, B; Paudel, R; Thapa, P; Shrestha, A; Poudyal, AK (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: Diabetes among tuberculosis patients is a growing concern. The prevalence of diabetes among tuberculosis patients in Nepal is not known. The objective of this study was to determine the prevalence of diabetes among tuberculosis patients and to identify the associated risk factors. Methodology: A descriptive, cross-sectional study was conducted in Kathmandu valley of Nepal. Face to face interviews using structured questionnaire were conducted to collect socio-demographic and behavioral risk factors. A random blood sugar test was carried out using glucometer. Measurements on height, weight and waist circumference were taken to obtain the anthropometric information. Results: Out of 407 tuberculosis patients recruited in the study, 37 (9.1%) were found to have diabetes. Among them 28 (6.9%) were self reported cases of diabetes while 9 (2.2%) were found with random blood sugar level >200mg/dl. Tuberculosis patients aged 50 years and above (OR 7.5; 95% CI 2.72-20.66), ever tobacco users (OR 3.5; 95% CI 1.19-10.74), high income status (OR 5.2; 95% CI 1.59-17.26) and self history of high blood pressure (OR 20.0; 95% CI 5.07-79.50) were found significantly associated with diabetes. Conclusion: Overall, the prevalence of diabetes among tuberculosis patients was 9.1%. Older age, tobacco use, high income status and history of high blood pressure were identified as associated risk factors. SAARC J TUBER LUNG DIS HIV/AIDS, 2015 XII (2), Page: 20-27